EFEKTIVITAS PENGGUNAAN METODE EL-SYARIF DALAM MENINGKATKAN KEMAMPUAN MENGHAFAL MUFRODAT SISWA DI MADRASAH IBTIDAIYAH AL-ISHLAH PALEMBANG - Delly Delly (Conciencia, 2017)
Low student learning outcomes, especially in terms of memorizing Mufrodat. To overcome this, a research was conducted by implementing the El Syarif method as an Experimental research with Design Pre-test Post-test. With one sample group, namely class V with t test (t-test). The result is pre-test thitung = -6.77 while the post test is 1.725 and for the level of error 1% the table is 1.325. The difference between the results of the pre-test and post-test was obtained tcount 18.64. This means that there has been a significant increase in mufrodat memorization results after the implementation of the El Syarif method.